Analisis Kinerja Keuangan Bank Syariah Indonesia Sebelum dan Sesudah Merger Menggunakan Metode Maqashid Shariah Index dan Profitabilitas - Jupriyansyah; Amrizal; Elinah; Iwan Subandi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Bank Syariah Indonesia was established on February 1,2021. The establishment of Bank Syariah Indonesia was a combination of 3 (three) BUMN Banks (State Owned Enterprises), namely Bank Syariah Mandiri, BNI Syariah, and BRI Syariah. For this reason, the merger of the three banks aims to realize efforts to build an advanced Islamic bank. On the other hand, the progress of an Islamic banking industry is certainly inseparable from the evaluation of the Islamic bank's financial performance. This aims to determine the financial conditions that occurred during a certain period, in which this information is intended for the government, investors and customers of the Islamic bank. So because of this, the authors are interested in measuring the performance of Indonesian Sharia Banks, which can still be said to be new because it is the result of the merger of the three state-owned banks based on the Maqashid Sharia Index and Profitability concept. This research aims to analyze the performance achievements of Bank Syariah Indonesia before and after the merger using the Maqashid Shariah Index and Profitabilta methods and to compare the two performance achievements. The results of the study found that after the Merger, Indonesian Sharia Banks achieved the highest average MSI Performance ratio (Maqashid Syariah Index) and Profitability Performance ratios compared to before the Merger.